1995
DOI: 10.1001/archpsyc.1995.03950220067013
|View full text |Cite
|
Sign up to set email alerts
|

The New York High-Risk Project

Abstract: Our data strongly support a specific familial liability to narrowly defined schizophrenia that is not shared by families of probands with affective disorder. Schizoaffective disorder and cluster A personality disorders, however, occur in families of both schizophrenic probands and probands with affective disorder. Psychotic affective disorders, which are not increased in HRSz subjects, do not appear to be an expression of the liability to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The systematic review identified 188 studies that provided prevalence estimates [18,29,36223]. These studies provided 1,721 estimates and were drawn from 46 countries.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review identified 188 studies that provided prevalence estimates [18,29,36223]. These studies provided 1,721 estimates and were drawn from 46 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Between them, the New York (63), the Copenhagen high-risk projects (64), and a notable Israeli study (65) have provided evidence of lifetime incidences of narrowly defined schizophrenia at between 8 and 21%. While low, these rates constitute significantly elevated incidence rates relative to the sporadic incidence in the population (~1–2%).…”
Section: Stress and The Risk State For Schizophreniamentioning
confidence: 99%
“…Most of the social consequences of the disorder occur in this early period of the course of schizophrenia. Congruently, high-risk and population cohort studies revealed that subjects who later develop schizophrenia have mild cognitive, motor, and social deficits from early childhood on as precursors of the disorder (e. g. Walker et al 1995;Jones et al 1994;Parnas et al 1993;Erlenmeyer-Kimling et al 1995). At the same time, it has been shown that delayed treatment is associated with significant disadvantages for schizophrenia patients, often resulting in functional and social decline (e. g. Wyatt 1997; Yung et al 1998;Bottlender and Möller 2003).…”
Section: Early Detection and Early Interventionmentioning
confidence: 99%